2017
DOI: 10.3892/etm.2017.5498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PrP105‑132 on the secretion of interleukin‑6 and interleukin‑8 from microglial cells in�vitro

Abstract: Abstract. In the present study, the effect of prion protein (PrP) on the secretion of interleukin-6 (IL-6) and IL-8 from microglial cells in vitro and its possible underlying pathway were investigating by establishing a cell model for prion disease. Rat neuroglial cells were cultured in vitro, and were treated with 80 µM PrP peptides 105-132 (PrP105-132) only, PrP+MG132 or PrP+cyclosporin A (CsA). After 48 h, the IL-6 and IL-8 levels in the supernatant fluid of the treated cells were detected using enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated the effect of treatment of toxic PrP peptide in inducing microglia activation and cytokine release (135). Garcao and colleagues showed that treatment of microglia led to increased IL-6 secretion, responsible for increased neuronal death (136,137). Interestingly, none of the antibody treatment following DMT were able to affect the production and increase of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the effect of treatment of toxic PrP peptide in inducing microglia activation and cytokine release (135). Garcao and colleagues showed that treatment of microglia led to increased IL-6 secretion, responsible for increased neuronal death (136,137). Interestingly, none of the antibody treatment following DMT were able to affect the production and increase of TNF-a.…”
Section: Discussionmentioning
confidence: 99%